STEP - BY - STEP EXPLANATION
What to find?
The average rate of change of the given function.
Given:
Step 1
State the average rate of change formula.
![Average\text{ rate of change=}(f(x_2)-f(x_1))/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/7tra7sf2k92uqy875sba1u9w5jwqo1eqwa.png)
Step 2
Determine the values of the function at the given interval.
Let x₁ = -4 and x₂ = -1
Locate f(x₁) and f(x₂) on the graph given.
f(x₁) = 4 and f(x₂)= -2
Step 3
Substitute the values into the formula and simplify.
![Average\text{ rate of change=}(-2-4)/(-1+4)](https://img.qammunity.org/2023/formulas/mathematics/college/2lmre81lfmn48wucz6dd89hyx0hj7lq5a7.png)
![=(-6)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/35t7kq6b8qeyi55dgqukiwr7csuasds4ex.png)
![=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/jm542osl1bj5mi16mxi3azzmsja48ky9c1.png)
ANSWER
Average rate of change = -2